PREVALENT AND INCIDENT PHYSICAL AND COGNITIVE INDEPENDENCE AMONG THE OLDEST OLD: THE LONG LIFE FAMILY STUDY. (11th November 2018) - Santanasto, A J; Marron, M M; Wojczynski, M; Schupf, N; Sebastiani, P; Cosentino, S; Christensen, K; Newman, A B
Abstract: We examined 7-year change in prevalence of physical (no difficultly performing ADLs), cognitive (Mini Mental State Examination score ≥23) and overall independence (physically and cognitively independent) in LLFS subjects aged 90 ± 6 years. At baseline (n=1442), 84%, 85% and 71% were physically, cognitively and overall independent, respectively. After 7-years, 951 (66%) died and 108 (8%) were lost to follow-up. Importantly, 92% of those lost to follow-up compared to 60.0% of those who died had baseline independence. Among 7-year survivors, the prevalence of physical, cognitive and overall independence was 74%, 82% and 61%, respectively. Of those physically, cognitively and overall independent at baseline, 78%, 86%, and 69% remained independent. Prevalence increased by just 10% despite the 31% incidence among 7-year survivors, mainly attributable to high mortality risk among those dependent at baseline. A large proportion of this cohort remained independent, which supports further investigation of factors underlying preserved function at extreme ages.